2022
DOI: 10.4132/jptm.2022.05.16
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative disorder involving body fluid: diagnostic approaches and roles of ancillary studies

Abstract: Lymphocyte-rich effusions represent benign reactive process or neoplastic condition. Involvement of lymphoproliferative disease in body cavity is not uncommon, and it often causes diagnostic challenge. In this review, we suggest a practical diagnostic approach toward lymphocyte-rich effusions, share representative cases, and discuss the utility of ancillary tests. Cytomorphologic features favoring neoplastic condition include high cellularity, cellular atypia/pleomorphism, monomorphic cell population, and freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Among all the lymphomas, body fluids are more commonly involved by NHL than Hodgkin lymphoma (HL). Many studies have reported that fluid involvement by B‐cell NHL was more commonly observed than T‐cell NHL 6 . Diagnosis of fluid involvement by lymphoma is straight forward in already diagnosed/biopsy proven cases of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all the lymphomas, body fluids are more commonly involved by NHL than Hodgkin lymphoma (HL). Many studies have reported that fluid involvement by B‐cell NHL was more commonly observed than T‐cell NHL 6 . Diagnosis of fluid involvement by lymphoma is straight forward in already diagnosed/biopsy proven cases of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have recommended diagnostic algorithms to systematically approach lymphoid cell‐rich effusions/fluids 6,8 . Fluids involved by BL show uniform population of medium to large‐sized lymphoid cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infiltration of the lining of serous cavities in the body results in effusion which can be due to either benign or malignant causes. 1,2 Among malignant pleural effusions, ascites lymphoma accounts for 10.0-15.0% followed by lung, breast, and ovary carcinoma. 1 Patients with pleural effusions present with respiratory distress and require immediate therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Among malignant pleural effusions, ascites lymphoma accounts for 10.0-15.0% followed by lung, breast, and ovary carcinoma. 1 Patients with pleural effusions present with respiratory distress and require immediate therapeutic intervention. [2][3][4] Pleural fluid analysis along with cytological examination is the readily available and cost-effective method of investigation for unilateral pleural effusions.…”
Section: Introductionmentioning
confidence: 99%